Higher frequency of interstate over international transmission chains of SARS-CoV-2 virus at the Rio Grande do Sul - Brazil state borders - Filipe Zimmer Dezordi; José Valter Joaquim Silva Júnior; Terimar Facin Ruoso; Angela Giovana Batista; Pedro Mesquita Fonseca; Larissa Paim Bernardo; Richard Steiner Salvato; Tatiana Schäffer Gregianini; Thaísa Regina Rocha Lopes; Eduardo Furtado Flores; Rudi Weiblen; Patrícia Chaves Brites; et al. (Virus Research)
Brazil's COVID-19 response has faced challenges due to the continuous emergence of variants of concern (VOCs), emphasizing the need for ongoing genomic surveillance and retrospective analyses of past epidemic waves to reassess and fine tune containment protocols. Rio Grande do Sul (RS), Brazil's southernmost state, has international borders and trades with Argentina and Uruguay, along with significant domestic connections within Brazil. The identification of source and sink transmission chains at national and international scales can identify main hubs and pathways to target future interventions. In this study we investigated the RS state role in the national and international SARS-CoV-2 transmission chains, which has not been fully explored. Nasopharyngeal samples from various municipalities in RS were collected between June 2020 and July 2022. SARS-CoV-2 whole genome amplification and sequencing were performed using high-throughput Illumina sequencing. Bioinformatics analysis encompassed the development of scripts and tools to perform subsampling taking into account epidemiological information to reduce sequencing disparities bias among the regions/countries, genome assembly, and large-scale alignment and phylogenetic reconstruction. We sequenced a total of 1,480 SARS-CoV-2 genomes from RS, covering all major regions. Sequences predominantly represented Gamma (April-June 2021) and Omicron (January-July 2022) lineages. Phylogenetic analysis revealed a regional pattern for transmission dynamics, particularly with Southeast Brazil for Gamma, and a range of inter-regional connections for Delta and Omicron within the country. On the other hand, international and cross-border transmission with Argentina and Uruguay was rather limited. We evaluated the three VOCs circulation over two years in RS using a new subsampling strategy based on the number of cases in each state during the circulation of each VOC. In summary, the retrospective analysis of genomic surveillance data demonstrated that virus transmission was less intense between country borders than within the country. These findings suggest that while non-pharmacological interventions were effective to mitigate transmission across international RS land borders, they were insufficient to contain transmission at the domestic level.